1985
DOI: 10.1093/bja/57.10.976
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroergotamine in the Prevention of Hypotension Associated With Extradural Anaesthesia

Abstract: The efficacy of a single dose of dihydroergotamine (DHE) 0.5 mg i.v. in preventing the decrease in arterial pressure resulting from extradural anaesthesia was studied in 47 patients; 24 received DHE and 23 a placebo, in a randomized double-blind manner. Although the decrease in systolic arterial pressure was more pronounced in the placebo group than in the DHE group, the difference was not significant. Diastolic and mean arterial pressures were both significantly lower in the placebo group than in the DHE grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Crystalloid fluid and albumin solutions have also been shown to be useful in parturients [13,14], in whom inferior vena caval compression may complicate the findings. Others have studied vasopressors, but their control patients received a fluid preload which did not prevent hypotension [15][16][17]. One study observed a decrease in arterial pressure of 24.7% and 15.2% with 0.75% bupivacaine and 0.5% amethocaine, respectively, despite 500-800 ml of crystalloid preload [18].…”
Section: Discussionmentioning
confidence: 99%
“…Crystalloid fluid and albumin solutions have also been shown to be useful in parturients [13,14], in whom inferior vena caval compression may complicate the findings. Others have studied vasopressors, but their control patients received a fluid preload which did not prevent hypotension [15][16][17]. One study observed a decrease in arterial pressure of 24.7% and 15.2% with 0.75% bupivacaine and 0.5% amethocaine, respectively, despite 500-800 ml of crystalloid preload [18].…”
Section: Discussionmentioning
confidence: 99%